(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Diversity management and the Upper Echelons Theory (UET) are essential in analysing the need for specific leadership compositions to strategically impact enterprises' financial performance. Authors consider that diversity management emphasizes fostering inclusivity and social integration, whereas UET envisions that top management team (TMT) characteristics directly influence corporate decisions and financial outcomes. The article highlights synergies and identifies differences in approaches and future research directions, striving to interlink these concepts for the applicability in practice. This conceptual literature review examines academic articles, as well as PhD theses, selected by keywords. Studies on the Diversity Management (DM) concept and articles related to the Upper Echelons Theory (UET) were selected based on relevance. The findings suggest that diverse top management teams enhance strategic decision-making by integrating varied capabilities and knowledge in the team, which serves for better strategic decision-making, affecting the financial outcomes of the enterprise, and in particular, it is beneficial in times of crisis. Effective diversity management extends beyond demographic factors, setting the need to incorporate education, experience, and other cognitive attributes emphasized in UET. As an asset, there is also the need to look further at the social networks of top management team members, shaping management strategies and the financial performance of the Top management team members. Even though there is significant literature in the diversity management field, the links between surface-level and deeper-level diversity management are lacking. Studies often treat the concept of Diversity Management and UET as separate domains, except for gender issues, limiting the potential to integrate those insights fully. The article advocates a shift beyond the traditional concept of diversity, equity, and inclusion (DEI) perspectives and strives to develop an overarching understanding of diversity as a combination of surface-level diversity and competencies people acquire, by introducing a new concept - systemic diversity management.